2020
DOI: 10.1371/journal.pone.0240166
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of the log linear association between LDL-C lowering and cardiovascular risk reduction: Greatest benefits when LDL-C >100 mg/dl

Abstract: Background The log linear association between on-treatment LDL-C levels and ASCVD events is amplified in higher risk patient subgroups of statin versus placebo trials. Objectives Update previous systematic review to evaluate how the log linear association influences the magnitude of cardiovascular risk reduction from intensifying LDL-C lowering therapy. Methods MEDLINE/PubMED, Clinical trials.gov, and author files were searched from 1/1/2005 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 50 publications
(84 reference statements)
0
8
0
Order By: Relevance
“…Even with low baseline LDL-C, statin therapy improves clinical prognosis [6][7][8][9]. But the bene t is less prominent as compared with high LDL-C, and recurrent vascular events continue to occur [3,4], which suggests other risk factors, rather than LDL-C, are involved in atherosclerosis progression for those patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even with low baseline LDL-C, statin therapy improves clinical prognosis [6][7][8][9]. But the bene t is less prominent as compared with high LDL-C, and recurrent vascular events continue to occur [3,4], which suggests other risk factors, rather than LDL-C, are involved in atherosclerosis progression for those patients.…”
Section: Discussionmentioning
confidence: 99%
“…The higher the baseline LDL-C is, the more bene ts derived from lipid-lowering therapy. Cardiovascular bene ts from intensi ed lipid-lowering therapy are expected less in those with baseline LDL-C < 100 mg/dl [3,4]. Serial intravascular ultrasound analysis also indicates that statin therapy is less effective in inducing coronary plaque regression in patients with low LDL-C [5].…”
Section: Introductionmentioning
confidence: 99%
“…Copyright 2021 KEI Journals. All Rights Reserved https://esmed.org/MRA/mra/ the "iconoclasts" of the LDL-centric principle and the benefit of statins 25,26 ; d) attraction to new strategies such as monoclonal antibodies (mAbs) or antisense oligonucleotides (ASOs) and small interfering RNAs (siRNAs), many of them still in the research phase and many others, although already approved for clinical use, with inappropriate balances between saving and spending, especially in primary cardiovascular prevention or in patients with LDL-C <100 mg/dL in treatment with statins 27 ; the latter, the main limitation to access these new strategies, even in countries like the United States 28 ; e) and finally, the proliferation of so-called generic and "similar" statins whose therapeutic efficacy is presumed by a single bioequivalence study (generic) or by the active ingredient included in the label (similar), without any other pharmacokinetic or pharmacodynamic evaluation. 29 In addition, the use of some naturopathic products that have been approved by the Federal Commission for the Protection of Sanitary Risks in Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…The higher the baseline LDL-C is, the more benefits derived from lipid-lowering therapy. Cardiovascular benefit from intensified LDL-C lowering was expected less in patients with baseline LDL-C <100 mg/dL 3 4. Serial intravascular ultrasound analysis also indicated that statin therapy in inducing coronary plaque regression was less effective in patients with low LDL-C 5.…”
Section: Introductionmentioning
confidence: 99%